Предмет: Математика,
автор: Ninara06
Решите уравнения:
a)(x-3)²+(x + 1)² =10
b)(x - 2)² +х (х + 4) =22
Ответы
Автор ответа:
2
Ответ:
Пошаговое объяснение:
a)(x-3)²+(x + 1)² =10
x² - 6x + 9 + x² + 2x + 1 = 10
2x² - 4x + 10 = 10
2x² - 4x = 0
2x*(x - 2) = 0
2x = 0 или x - 2= 0
x₁ = 0 ; x₂ = 2
b)(x - 2)² +х (х + 4) =22
x² - 4x + 4 + x² + 4x = 22
2x² + 4 = 22
2x² = 18
x² = 9
x₁ = -3 ; x₂ = 3
Похожие вопросы
Предмет: Алгебра,
автор: TonyBlack
Предмет: Алгебра,
автор: morenkoff
Предмет: Биология,
автор: tigri199789
Предмет: Қазақ тiлi,
автор: eturdygazina